EPISOMIC ELEMENT IN A STRAIN OF SALMONELLA TYPHOSA - Falkow, Stanley (1962)
Falkow, Stanley (Walter Reed Army Institute of Research, Washington, D.C.) and L. S. Baron. Episomic element in a strain of Salmonella typhosa. J. Bacteriol. 84:581–589. 1962.—An episomic element, F(0)-lac(+), has been identified in a strain of Salmonella typhosa isolated from a natural habitat. The F(0)-lac(+) element is transferred at high frequency as a single unit of transmission and replication without linkage to any other genetic character. Cells receiving F(0)-lac(+) are heterogenotes as if F(0)-lac(+) is not integrated as part of the linear structure of the chromosome, but rather replicates autonomously or in some other association with the genome. Evidence from complementation tests and transduction experiments is presented that the lac genes carried by F(0) are identical or at least markedly similar to the lac genes of Escherichia coli K-12. The F(0) transmission factor cannot be precisely identified but it does not appear to be phage or colicin. F(0) does exhibit mutual repression with the sex factor, F, of E. coli, and immunological experiments indicate some relationship between F and F(0).